Contemporary Notions: Ibn Khaldun’s ‘AsabiyyahRevisited - Mohd Tohar, Siti Nor Azhani; Razali, Asbah; Latiff, Latifah (Journal of Techno-Social, 2019)
The phrase’asabiyyahwasprofoundly foregrounded600 years ago by Ibn Khaldun in his magnum opus, theMukadimah, as the principal determinant to the rise and fall of a civilisation. Nevertheless, the debate on contemporary concepts such as nationalism, patriotism, national identity and sense of belonging are adopted in addressing statehood and nation which are deeply related to the discussion of Ibn Khaldun’s’asabiyyah. Accordingly, this article presents the revisiting act of discussing Ibn Khaldun’s ‘asabiyyahwithin contemporary notions. This discussion involves a qualitative approach through content analysis from various literatures wh ich considers the views of scholars on the concepts of patriotism, nationalism, national identity and sense of belonging and these concepts were derived from Ibn Khaldun’s’asabiyyah. Ergo, many scholars have recognised the contribution of Ibn Khaldun's’asabiyyah, and it stays relevant in today’s contemporary concepts